Hydrolyzed Protein Formula for Allergy Prevention in Preterm Infants: Follow-Up Analysis of a Randomized, Triple-Blind, Placebo-Controlled Study - Antonio Di Mauro; Maria Elisabetta Baldassarre; Giulia Brindisi; Anna Maria Zicari; Martina Tarantini; Nicla Laera; Manuela Capozza; Raffaella Panza; Silvia Salvatore; Licia Pensabene; Margherita Fanelli; Nicola Laforgia (Frontiers Media S.A., 2020)
Background: Allergic diseases are a major public health burden worldwide. Evidence suggests that early nutrition might play a key role in the future development of allergies and the use of hydrolyzed protein formulas have been proposed to prevent allergic disease, mainly in term infants with risk factors.Aim: To evaluate the preventive effect of a hydrolyzed protein formula vs. an intact protein formula on allergy development in preterm infants with or without risk factors.Methods: We performed a 3-year follow-up study of a previous triple-blind, placebo-controlled randomized trial. Evidence of atopic dermatitis, asthma and IgE-mediated food allergies were evaluated according to a validated parental questionnaire (Comprehensive Early Childhood Allergy Questionnaire). Food sensitization was also investigated by skin prick test at 3 years of chronological age.Results: Of the 30 subjects in the intact protein formula group and 30 in the extensively hydrolyzed formula group, respectively 18 and 16 completed the 3-year follow-up and entered the final analysis. No group differences in the incidence of atopic dermatitis, asthma, IgE-mediated food allergies, and food sensitization were found.Conclusion: Despite the small number of cases, extensively hydrolyzed protein formula seems to be ineffective in allergic diseases prevention in preterm neonates. Further adequately powered, randomized controlled trials evaluating hydrolyzed protein formula administration to prevent allergic diseases in preterm neonates are needed.